IMPLEMENTATION OF THE MASS APPRAISAL SYSTEM FOR REAL ESTATE IN UZBEKISTAN (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
Dedicated to analyzing the significance, problems, and prospects of implementing a public property valuation system in Uzbekistan. The study examines the theoretical foundations of the public property valuation system, the state and features of the real estate market in Uzbekistan, its main directions, the significance, problems, and prospects of implementing the system. Proposals and recommendations for the implementation of the system were also given.